2003
DOI: 10.1093/jpepsy/jsg016
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Does Posttraumatic Stress Apply to Siblings of Childhood Cancer Survivors?

Abstract: Levels of PTS are elevated for siblings of childhood cancer survivors. Thus, PTS may be a useful model for understanding siblings' long-term reactions to cancer. Future research and clinical efforts should consider the needs of siblings of childhood cancer survivors in a family context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
110
3
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(127 citation statements)
references
References 18 publications
5
110
3
6
Order By: Relevance
“…This attests to children's resilience to the effects of traumatic medical experiences. Still, the fact that siblings in general tended to have more internalizing problems (anxiety, depression and social withdrawal) than survivors supports some earlier 11 and recent reports on post-traumatic stress symptoms in siblings of children with cancer, 10 and suggests that some siblings, in fact, were reported to have internalizing scores in the clinical range.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…This attests to children's resilience to the effects of traumatic medical experiences. Still, the fact that siblings in general tended to have more internalizing problems (anxiety, depression and social withdrawal) than survivors supports some earlier 11 and recent reports on post-traumatic stress symptoms in siblings of children with cancer, 10 and suggests that some siblings, in fact, were reported to have internalizing scores in the clinical range.…”
Section: Discussionsupporting
confidence: 69%
“…[5][6][7][8][9] Other studies have found no differences between survivors of childhood cancer and their healthy siblings in behavioral, educational and social problems, as well as feelings of distress, guilt and psychosomatic symptoms. [10][11][12][13] In contrast, in an early study, siblings of childhood cancer survivors showed more distress than the survivors in perceived social isolation; 11 or survivors performed like their siblings in psychological adjustment but did significantly worse than their siblings in educational outcomes. 14 A recent study examining post-traumatic stress found that siblings reported more symptoms of post-traumatic stress than did childhood cancer survivors.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…This impact is even higher when one of the brothers or sisters is struggling with a malign cancer. The results of this research are consistent with earlier results (Horwitz & Kazak, 1990;Sahler et al, 1994;Alderfer et al, 2003;Houtzager et al, 2004), when we found increased problems of internalization and externalization in comparison to the control group. At the same time, we received new results which might bring us closer to a deeper understanding of this complex process, with a special respect to the projective drawing analysis that we have used.…”
Section: Discussionsupporting
confidence: 93%
“…Stuber et al (1996) found that more than half of their sample of childhood cancer survivors reported posttrauma symptoms including bad dreams and feeling afraid or upset when thinking about cancer. A series of reports has documented PTSS and/or PTSD in mothers of childhood cancer survivors Brown et al, 2003;Kazak et al, 1997Kazak et al, , 1998Kazak et al, , 2004Manne et al, 1998Manne et al, , 2002Pelcovitz et al, 1996) as well as in their fathers and siblings (Alderfer et al, 2003).…”
Section: Introductionmentioning
confidence: 99%